TEMPORAL DYNAMICS OF CO2 EFFLUX AND LITTER DEPOSITION IN A DRY TROPICAL FOREST IN THE BRAZILIAN SEMIARID REGION - Costa, Cassio Ricardo Gonçalves da; Silva, Marcos Gomes da; Marques, Ailson De Lima; Moura, Debora Coelho; Macedo, Rodrigo Santana; Sousa, Gabryelle de Farias (Revista Valore, 2023)
The study of the dynamics of the Caatinga ecosystem, which includes the process of nutrient cycling through the contribution and litter decomposition, and the microbial activity measured through CO2 efflux, can contribute to a better understanding of the ecological processes in this ecosystem. Thus, the present study sought to quantify the contribution of the litter forming material and its chemical composition, and CO2 efflux from soil respiration in an area of shrubby-tree caatinga. A transect with 3 arborescent stratum sampling points and 3 shrubby strata, totaling 6 sampling points (2 environments x 3 points per environment x 3 replications per point) was drawn. The litter production was collected monthly (October 2017 to October 2018), using 6 collectors. The monthly CO2 emission was evaluated by the static closed chamber method. The influence of rainfall, soil moisture and temperature on the studied variables was evaluated. The annual litter production was estimated at 590 kg ha-1 for arboreal species and 767 kg ha-1 for shrubby species, and this layer is responsible for 23% more in the supply of plant material in the area. The highest CO2 emissions were found in the environment of shrubby vegetation with one annual total of 21.2 μmol m-2s-1 in relation to the area of arboreal vegetation that obtained 17.6 μmol m-2s-1. Spatial and temporal variability were observed in all analyzed variables and the strong influence of climatic factors such as precipitation, humidity and soil temperature.